Evaluation of ridge gourd hybrids for growth and yield attributes (Indian Journal of Arid Horticulture, 2025)
Ridge gourd [Luffa acutangula (Roxb.)L.] is an important cucurbitaceous vegetable grown during kharif and summer seasons in Andhra Pradesh. The tender fruits are used as vegetable and they are good source of vitamin A, B and C and also iron. Ridge gourd, being Ridge gourd, being predominantly monoecious and is cross-pollinated crop and provides ample scope for utilization of the hybrid vigor (Hedau and Sirohi, 2004). The present era is of hybrids and moreover the glut due to monocropping of tomato over larger acreage demands for crop diversification to make the profession of vegetable production is an economic one. Abusaleha and Dutta (1994) and Kadem et al. (1995) have reported that hybrids were early and gave higher yields in ridge gourd. The hybrids are fast replacing the commercial varieties because the private seed industry is emerging on the scene whose survival essentially depends on F, hybrids as the vegetable growers are bound to purchase the seed every year. To conclude on the performance of any genotype is often inconclusive because of inconsistent performance across environments.
Keywords: genotype; emerging; Abusaleha; monocropping; predominantly; monoecious